Effect of deposition temperature on the corrosion behavior of CVD SiC coatings on SiCf/SiC composites under simulated PWR conditions. (1st April 2021) - Qin, Yiming; Li, Xiaoqiang; Liu, Chuanxin; Zheng, Ce; Mao, Qingping; Chen, Bo; Jing, Ke; Tan, Yaru; Cheng, Laifei; Zhang, Litong
Graphical abstract: Highlights: The rise of deposition temperature improves the corrosion resistance of coatings. The corrosion resistance depends on the grain size and crystallinity of coatings. Two different corrosion mechanisms are proposed based on characterization results. Abstract: To improve the hydrothermal corrosion resistance of SiCf /SiC composites, SiC coatings were chemical vapor deposited at 1000, 1150 and 1200 °C. Their corrosion behaviors were investigated using immersion tests and various analytical methods. The intergranular corrosion phenomenon was observed at all three coatings. It caused the delamination on the surface of 1000 and 1150 °C coatings, whereas only the local fall-off of large grains occurred on the 1200 °C coating. The large grain size and high crystallinity of coating deposited at 1200 °C contributed to the excellent corrosion resistance compared with coatings deposited at other two temperatures.